Community-Based Sustainable Tourism as a Pillar of Tetebatu Village Development - Andrinata, Andrinata (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
Sustainable tourism activities involve interactions between local communities and tourists. One of the concepts used in sustainable tourism development is Community-Based Tourism. This concept requires the contribution and active participation of local communities in tourism development. The research aims to explain how the concept of sustainable tourism through the Community-Based Tourism approach as an effort in community economic development. This research is a type of qualitative research with an ethnographic approach. The ethnographic approach is intended to reveal the meaning of the behavior or actions of a group of people related to the historical and social and cultural background. The form of community participation in tourism activities carried out in Tetebatu Tourism Village is more about the energy, thoughts, and expertise possessed by each community member. Each community member is involved in existing tourism groups such as tourism awareness groups (Pokdarwis), culinary provider groups, farmer groups, homestay groups, livestock groups, arts groups, craftsmen groups, and tour guide groups.